Implementation of the Savvy portable ECG body monitor for cardiac arrhythmia screening at the primary health care level: an interventional randomized controlled trial - Vodička, Staša (Anali PAZU, 2023)
At the Jožef Štefan Institute, in cooperation with doctors, they developed a personal portable EKG meter Savvy, which works in combination with a smartphone and can be used in patients who complain of heart rhythm disorders. The aim of the study was to analyze the utility of telecardiology at the primary health care level using the Savvy portable ECG body monitor. Methods: We included 400 patients with a suspected heart rhythm disorder who visited their family doctor in the Ljubljana Health Center and the Murska Sobota Health Center from October 2016 to January 2018. The patients were divided into a test group, where they received a portable ECG body meter, and a control group, where they did not. Results: The study showed that there was no statistically significant difference between the test and control groups regarding detected rhythm disturbances and measures to treat patients, either by observation or by administering a new drug. In the test group, there were significantly fewer referrals to a cardiologist than in the control group (p <0.001).